Habits of energy drink consumption among teens in Slovenia - Focus group findings - Lorenzi Dominika Slokar De; Kovač Milena Blaž; Koch Verena (Sciendo, 2021)
Teachers in Slovenia have been noticing the increased consumption of energy drinks among pupils. Therefore, the purpose of this study was to investigate habits that contribute to the frequency of energy drink consumption.